Atypical case of mycoplasma pneumoniae presenting as Stevens-Johnson syndrome - Sharma, Kalpana; Das, Sinthiya; Basumatary, Phoebe Sarah (International Journal of Research in Medical Sciences, 2024)
Mycoplasma pneumoniae causes atypical pneumoniae in children and adolescents. M. pneumoniae associated Stevens-Johnson Syndrome (SJS) is also known as atypical SJS. SJS is characterized by generalised exanthema associated with fever, mucositis and history of numerous medications and certain agents of atypical pneumonia. We describe the case of a 7-year-old boy with bilateral atypical pneumonia along with multiple skin and mucosal exanthema that required intensive care unit admission due to respiratory distress. He was diagnosed with SJS associated atypical pneumonia caused by Mycoplasma pneumoniae confirmed by serological test. Since, there are few similar cases in literature; a treatment protocol is yet to be established. Our case is an example evidence-based treatment and hopefully in future there might be a definite protocol for Atypical Stevens-Johnson Syndrome.